Naïve T cells correlate with mucosal healing in patients with inflammatory bowel disease. (January 2013) - Karlsson, Mats; Linton, Ludvig; Lampinen, Maria; Karlén, Per; Glise, Hans; Befrits, Ragnar; Janczewska, Izabella; Carlson, Marie; Winqvist, Ola; Eberhardson, Michael
Abstract Background. In previous studies, adaptive immune responses involving T-helper cells have been shown to play an important role in inflammatory bowel diseases (IBDs). Methods. The aim of this study was to investigate any correlation between the degree of mucosal inflammation and the phenotype of gut-infiltrating T-helper cells. Biopsies from intestinal mucosa were obtained and intestinal T cells were analyzed with regard to activity and maturation markers. Patients with active colitis (39 with Crohn's disease and 47 with ulcerative colitis) were included and treated with corticosteroids, biologicals or leukocytapheresis. Flow cytometry was used to analyze activation marker expression on gut-infiltrating T-helper cells. Results. Mucosal healing was reflected by almost 100% increase of CD62L expression in mucosal T cells in patients in remission compared to those with active inflammation (p < 0.01). The frequency of mucosal-naïve CD4+CD45RA+ T cells was reduced by 50% in mucosa displaying remission (5.3% compared to 12% of the total amount and CD4+ T cells, p < 0.001). Surprisingly, the proportion of early activated T-helper cells (CD4+CD69+) did not differ between mucosa in remission and non-remission (43% and 42%, respectively). Moreover, no change in memory T-helper cells (CD4+CD45RO+) was observed (64% compared to 66%). The findings were independent of diagnosis (Crohn's disease or ulcerative colitis) or mode of treatment. Conclusion. This study suggests that a reduced recruitment of naïve T-helper cells and increased frequency of T-helper cells with lymph node homing marker expression reflect mucosal healing in IBD. Surprisingly, the degree of activation of mucosal T-helper cells did not correlate with disease remission.